“Coercive Control and Domestic Violence Laws in Pakistan: A Feminist Legal Analysis of Legislative Gaps” - Saba Farid (Social Science Review Archives, 2025)
The criminal law in Pakistan remains locked in a myopic gaze, recognising domestic violence primarily through the visible injuries it can count and prosecute. This paper argues that such a framing is not merely incomplete but a complicit. It fails to name coercive control as the constitutive condition of abuse in many intimate relationships. In doing so, it both misrecognises the lived experience of countless women and reinscribes a legal narrative that privileges physicality over power. Through a critical reading of domestic violence statutes, judicial reasoning, and enforcement patterns in Pakistan, this study reveals how legal silences on coercive control sustain a patriarchal status quo. Drawing on feminist jurisprudence, doctrinal critique, and comparative insights from the UK, USA, and Australia, it argues that the law’s selective attentiveness does not simply neglect coercive control but authorises it. To remain silent on coercive control is to legitimise a form of violence that prospers in the shadows of legality. This paper, therefore, urges not just reform, but re-imagination.